Onshore and offshore wind energy an introduction - Lynn, Paul A. (John Wiley & Sons Ltd, 2012)
"This book uses academic content and rigor to introduce all relevant topics, from global wind resource and historical background, through to modern electricity generation and distribution, including the topical subject area of offshore systems"-- Provided by publisher.